2007
DOI: 10.1111/j.1442-2042.2007.01910.x
|View full text |Cite
|
Sign up to set email alerts
|

Our experience with third renal transplantation: Results, surgical techniques and complications

Abstract: Background: Despite the popularity of kidney transplantation in the current era, second and third kidney transplantation are not yet widely accepted and practiced. Each center has its own regulations and experiences and there is no accepted protocol for third kidney transplantation. We report here our 15 years of experience with third kidney transplantation. Methods: This is a report of all the third kidney transplantations performed in Baqiyatallah Hospital, Tehran, Iran, between 1991 and 2006. Demographic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
0
10
0
3
Order By: Relevance
“…Several retransplantation techniques have been described including the transperitoneal, retroperitoneal, and orthotopic approach (3)(4)(5)(6). This raises the question which technique has to be preferred.…”
Section: Introductionmentioning
confidence: 99%
“…Several retransplantation techniques have been described including the transperitoneal, retroperitoneal, and orthotopic approach (3)(4)(5)(6). This raises the question which technique has to be preferred.…”
Section: Introductionmentioning
confidence: 99%
“…All transplants were performed via the extraperitoneal approach which can be particularly challenging due to extensive scarring from previous surgery. Other approaches such as transperitoneal and orthotopic transplantation have been described to avoid this problem although we have not found it necessary to use these in our practice so far . The use of standardized pre‐operative vascular imaging may have contributed to this—in many cases, severe iliac disease was identified that became important in the subsequent planning of operative strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Significant fibrosis and scarring may hamper identification of correct tissue planes necessitating more complex vascular surgery and risking inadvertent collateral damage and complications. Anastomotic and overall operative times may be extended and have been associated with a detrimental impact upon morbidity …”
Section: Introductionmentioning
confidence: 99%
“…К недостаткам такого варианта можно отнести не-сколько больший риск сосудистых осложнений, так как в этой позиции трансплантат более моби-лен и его смещение или ротация может приводить к компрометации кровотока. Кроме того, послеопе-рационный период может осложниться кишечной непроходимостью, а при развитии мочевого затека или инфекционных осложнений в патологический процесс будет вовлечена брюшная полость [69,70].…”
Section: хирургические особенности повторных трансплантацийunclassified
“…По данным разных центров, частота хирургических осложнений варьирует от 0 до 37%. Также многие авторы сообщают о боль-шей кровопотере и продолжительности повторных трансплантаций почки [68][69][70][71][72].…”
Section: хирургические особенности повторных трансплантацийunclassified